2020
DOI: 10.2105/ajph.2020.305858
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of COVID-19–Related Racial Discrimination on the Health of Asian Americans

Abstract: Anti-Asian discrimination and assaults have increased significantly during the Coronavirus disease 2019 (COVID-19) pandemic, contributing to a “secondary contagion” of racism. The United States has a long and well-documented history of both interpersonal and structural anti-Asian discrimination, and the current pandemic reinforces longstanding negative stereotypes of this rapidly growing minority group as the “Yellow Peril.” We provide a general overview of the history of anti-Asian discrimination in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
192
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(228 citation statements)
references
References 19 publications
7
192
1
Order By: Relevance
“…Experiencing pandemic-related discrimination is associated with participants’ experience of pandemic-related stress. While our cross-sectional study does not establish a causal relationship between pandemic-related discrimination and stress, this finding echoes previous studies showing that discrimination can lead to negative and long-term consequences for mental health [ 3 , 10 , 15 , 33 – 35 ]. While societal strategies for decreasing discrimination are paramount, other researchers have also found that social support and coping strategies can buffer the immediate negative emotional impact of discrimination on Asian Americans [ 35 ].…”
Section: Discussionsupporting
confidence: 81%
“…Experiencing pandemic-related discrimination is associated with participants’ experience of pandemic-related stress. While our cross-sectional study does not establish a causal relationship between pandemic-related discrimination and stress, this finding echoes previous studies showing that discrimination can lead to negative and long-term consequences for mental health [ 3 , 10 , 15 , 33 – 35 ]. While societal strategies for decreasing discrimination are paramount, other researchers have also found that social support and coping strategies can buffer the immediate negative emotional impact of discrimination on Asian Americans [ 35 ].…”
Section: Discussionsupporting
confidence: 81%
“…Our respondents expressed higher levels of worry about violence during (vs before) the pandemic, ranging from 2.8 to 5.6 percentage point increases in the estimated statewide prevalence of adults who reported that they were somewhat or very worried about multiple types of interpersonal violence (ie, robbery, assault, homicide, police violence), suicide, and unintentional firearm injury happening to them. As expected, 15,16 self-reported experiences of unfair treatment attributed to the pandemic were also reported and disproportionately common among Asian respondents. In addition to worry about violence for oneself, 13.3% of respondents reported concern that someone they know might physically harm themselves on purpose.…”
Section: Discussionsupporting
confidence: 69%
“…[11][12][13][14] Fear and scapegoating associated with COVID-19 may increase biasmotivated unfair treatment. 15,16 During the summer of 2020, largely peaceful 17 protests decrying structural inequities, which contribute to both police violence and the uneven burden of COVID -19, have been met, at times, by law enforcement use of crowd-control weapons 18 and heavily armed white supremacist and far-right vigilantes. 19 While most major news sources reported initial decreases in violent incidents, as measured by local police calls for service, following pandemic-related lockdowns and stay-at-home orders, the latest indications are that more serious acts of violence, particularly those involving firearms, have remained the same or increased.…”
Section: Introductionmentioning
confidence: 99%
“…As times of crisis often reinforce and exacerbate these disparities because resources are limited and people are fearful, traditionally minoritized and marginalized populations (e.g., racial/ethnic minorities, low-income families, women) may encounter more challenges ( Kantamneni, 2020 ). As part of the long history of racial bias and discrimination in the U.S., national disasters and crises have often become racialized and scapegoated minority groups are targeted and blamed ( Chen et al, 2020 ). Evidently, racial discrimination against Asians and Asian Americans has increased significantly since the outbreak of the COVID-19 in the U.S.…”
mentioning
confidence: 99%
“…Evidently, racial discrimination against Asians and Asian Americans has increased significantly since the outbreak of the COVID-19 in the U.S. (e.g., Chen et al, 2020 ; Lee & Waters, 2020 ). According to a Pew Research Center survey, Black and Asian Americans have shared the experiences of racial discrimination amid the COVID-19 pandemic.…”
mentioning
confidence: 99%